A CROSS SECTIONAL STUDY ON PERCEPTION TOWARDS WELLNESS PRACTICE AMONG THE EMPLOYEES AT PRIVATE HOSPITAL (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Workplace wellness practices focus on  lowering employee risk by providing ongoing  health promotion and sickness management  because they allow for frequent contact with  employees through regulated environmental  and communication systems, workplaces are  perfect for health behaviour change. Here the  researchers tried to understand the employee’s  perception towards wellness practice, check  the employees’ interest in different wellness  practice and recommended to implement  employee wellness measures in the company.  A substantial amount of material was obtained  and then combined and concentrated in an  ethical manner in order to partially satisfy the  requirements for the academic research project.  This project was conducted in order to meet a  component of those specifications. Apart from  the guide and his student, researchers provided  significant contributions to this study work,  which served to make it more realistic.
Keywords: Perception; Wellness; Screening Test; Gender and Experience